Near collapse of the meridional SST gradient in the eastern equatorial Pacific during Heinrich Stadial 1. (25th November 2013) - Kienast, Stephanie S.; Friedrich, Tobias; Dubois, Nathalie; Hill, Paul S.; Timmermann, Axel; Mix, Alan C.; Kienast, Markus
Abstract [1] Sea surface temperatures (SST) and inorganic continental input over the last 25, 000 years (25 ka) are reconstructed in the far eastern equatorial Pacific (EEP) based on three cores stretching from the equatorial front (~0.01°N, ME0005‐24JC) into the cold tongue region (~3.6°S; TR163‐31P and V19‐30). We revisit previously published alkenone‐derived SST records for these sites and present a revised chronology for V19‐30. Inorganic continental input is quantified at all three sites based on 230Th‐normalized fluxes of the long‐lived continental isotope thorium‐232 and interpreted to be largely dust. Our data show a very weak meridional (cross‐equatorial) SST gradient during Heinrich Stadial 1 (HS1, 18–15 ka B.P.) and high dust input along with peak export production at and north of the equator. These findings are corroborated by an Earth system model experiment for HS1 that simulates intensified northeasterly trade winds in the EEP, stronger equatorial upwelling, and surface cooling. Furthermore, the related southward shift of the Intertropical Convergence Zone (ITCZ) during HS1 is also indicative of drier conditions in the typical source regions for dust.